2016
DOI: 10.5505/agri.2016.19870
|View full text |Cite
|
Sign up to set email alerts
|

The anatomical variation to be considered in upper extremity blocks: Double Axillary Vein

Abstract: E D İ T Ö R E M E K T U P / L E T T E R T O T H E E D I T O R PAIN A RISayın Editör, Üst ekstremite sinir blokları bu bölgenin kronik ağrı tedavisi ve cerrahisi için sık olarak uygulanan bir yön-temdir. [1][2][3] Kolay yapılabilir olması, olası komplikasyon gelişimini azaltması, yeterli blok için daha az lokal anestezik ihtiyacı olması gibi nedenlerle son yıllarda sinir bloklarının USG eşliğinde yapılması yaygınlık kazanmıştır. Karşılaştığımız unilateral çift axiller ven varyasyonunu tanımlamak ve intravaskule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Other than these, the current literature contains a single case report to represent detection of double axillary veins during peripheral nerve block intervention under ultrasound guidance, and another report describing a double axillary vein variation preoperatively diagnosed by CT 8 9. In these reports, the authors highlighted the importance of detailed knowledge of the axillary anatomy to avoid complications such as intravascular injection of local anaesthetics during peripheral nerve block interventions or injury to the vessels and nerves during surgical axillary dissection 5–8. Uysal et al reported that the use of hydro-location technique provided a safer area during infraclavicular nerve block intervention of a patient with double axillary vein 8.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other than these, the current literature contains a single case report to represent detection of double axillary veins during peripheral nerve block intervention under ultrasound guidance, and another report describing a double axillary vein variation preoperatively diagnosed by CT 8 9. In these reports, the authors highlighted the importance of detailed knowledge of the axillary anatomy to avoid complications such as intravascular injection of local anaesthetics during peripheral nerve block interventions or injury to the vessels and nerves during surgical axillary dissection 5–8. Uysal et al reported that the use of hydro-location technique provided a safer area during infraclavicular nerve block intervention of a patient with double axillary vein 8.…”
Section: Discussionmentioning
confidence: 99%
“…In these reports, the authors highlighted the importance of detailed knowledge of the axillary anatomy to avoid complications such as intravascular injection of local anaesthetics during peripheral nerve block interventions or injury to the vessels and nerves during surgical axillary dissection 5–8. Uysal et al reported that the use of hydro-location technique provided a safer area during infraclavicular nerve block intervention of a patient with double axillary vein 8. Hydro-location technique is a principle to locate needle-tip by using ultrasound liquid detection.…”
Section: Discussionmentioning
confidence: 99%